Effect of Occupational Safety and Health (K3), Work Discipline and Work Creativity on Employee Performance at PT. Tunggal Djaja Indah - Saiful Amir; Sihab Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze 1). the effect of occupational safety and health on the performance of employees at PT.Tunggal Djaja Indah, 2). the influence of work discipline affects the performance of employees at PT.Tunggal Djaja Indah, 3). the influence of work creativity affects the performance of employees at PT.Tunggal Djaja Indah, 4). The effect of occupational safety and health, work discipline and work creativity simultaneously has a significant effect on employee performance at PT.Tunggal Djaja Indah. The type of data used in this study is the type of quantitative data. The sampling technique used in this research is using the Slovin formula with a sample of 89 respondents at PT.Tunggal Djaja Indah. Analysis of the data used is multiple linear regression analysis, t-test and f-test. The results showed that the safety and health variables had a significant effect on employee performance at PT.Tunggal Djaja Indah, work discipline had a significant effect on employee performance at PT.Tunggal Djaja Indah